Relationship between virulence of Mycobacterium avium strains and induction of tumor necrosis factor alpha production in infected mice and in in vitro-cultured mouse macrophages. - Sarmento, A M (1995)
We studied the ability of two Mycobacterium avium strains with different virulences to induce tumor necrosis factor alpha (TNF) synthesis by mouse resident peritoneal macrophages (RPM phi) in vitro in an experiment to look for a possible correlation between virulence and this TNF-inducing capacity. The low-virulence strain, 1983, induced significantly higher production of TNF by RPM phi than did the high-virulence strain, ATCC 25291. TNF neutralization during culture of infected RPM phi resulted in enhancement of growth of strain 1983 and had no effect on growth of strain ATCC 25291; TNF treatment of strain ATCC 25291-infected macrophages had no effect on mycobacterial growth. The extent of M. avium growth and the amount of TNF synthesis were independent of the presence of contaminating T cells or NK cells in the macrophage monolayers. Intraperitoneal administration of anti-TNF monoclonal antibodies to BALB/c mice infected intravenously with M. avium 1983 abrogated the elimination of the bacteria in the liver and caused a slight increase in bacterial growth in the spleen. Neutralization of TNF led to a minor increase in the proliferation of M. avium ATCC 25291 in the liver and spleen of BALB/c mice late in infection. Anti-TNF treatment did not affect the growth of the two M. avium strains in BALB/c.Bcgr (C.D2) mice, suggesting that restriction of M. avium strains to induce TNF production by macrophages may limit their ability to proliferate both in vitro and in vivo.